Evolving paradigms in multifocal breast cancer. (April 2015) - Salgado, Roberto; Aftimos, Philippe; Sotiriou, Christos; Desmedt, Christine
Abstract: The 7th edition of the TNM defines multifocal breast cancer as multiple simultaneous ipsilateral and synchronous breast cancer lesions, provided they are macroscopically distinct and measurable using current traditional pathological and clinical tools. According to the College of American Pathologists (CAP), the characterization of only the largest lesion is considered sufficient, unless the grade and/or histology are different between the lesions. Here, we review three potentially clinically relevant aspects of multifocal breast cancers: first, the importance of a different intrinsic breast cancer subtype of the various lesions; second, the emerging awareness of inter-lesion heterogeneity; and last but not least, the potential introduction of bias in clinical trials due to the unrecognized biological diversity of these cancers. Although the current strategy to assess the lesion with the largest diameter has clearly its advantages in terms of costs and feasibility, this recommendation may not be sustainable in time and might need to be adapted to be compliant with new evolving paradigms in breast cancer.